Ladakh, kingdom of sustainable development? - David Goeury (Revue de Géographie Alpine)
With some 15,000 km² of protected areas, Ladakh has become synonymous with biodiversity protection in India. Specific regulations have been drawn up for the region to ensure preservation of the natural environment. Local officials who contested the principles of India’s hard law have benefited from the initiatives of numerous NGOs and have developed an alternative model for protecting the environment. Certain large emblematic mammals like the snow leopard have enabled the legitimisation of a policy that is based on the participation of local inhabitants rather than on their eviction to areas outside the sanctuaries. The protected areas have thus become an element of a Ladakhi identity project that distinguishes the region with respect to Kashmiri regional power.